2020
DOI: 10.1002/14651858.cd013665
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms to determine if a patient presenting in primary care or hospital outpatient settings has COVID-19 disease

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
443
1
22

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(489 citation statements)
references
References 34 publications
23
443
1
22
Order By: Relevance
“…There are four statuses namely Green, Yellow, Orange and Red of which Singapore is at orange currently which meant that the disease is severe but has not spread widely and is being contained Pregnant women should also avoid missing prenatal appointments if well and limit interactions with others to reduce the risk of transmission. Symptomatic women should be urged to be tested early for COVID-19 by nasopharyngeal or oropharyngeal swabs and practice self-isolation to reduce the risk of vertical transmission [18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four statuses namely Green, Yellow, Orange and Red of which Singapore is at orange currently which meant that the disease is severe but has not spread widely and is being contained Pregnant women should also avoid missing prenatal appointments if well and limit interactions with others to reduce the risk of transmission. Symptomatic women should be urged to be tested early for COVID-19 by nasopharyngeal or oropharyngeal swabs and practice self-isolation to reduce the risk of vertical transmission [18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease (COVID- 19) is an infectious disease caused by a newly discovered severe acute respiratory syndrome coronavirus (SARS-CoV-2) rst identi ed in Wuhan City, China, in December 2019 [1]. On 11 th March 2020, the World Health Organization (WHO) declared the COVID-19 outbreak as a global pandemic with exponential spread worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
“…In total, searches identified 32 symptoms associated with COVID-19 presentation from 10 guidelines, 1 , 3 , 15 – 22 13 published reviews, 23 35 and 12 preprint reviews. 36 47 See Table 1 for the list of symptoms and proposed corresponding SNOMED CT codes.…”
Section: Resultsmentioning
confidence: 99%
“…Areas that merit further study include the causal relationship between the infection and skin lesions, the role of pathogenic mechanisms, the absolute frequency and the frequency of skin lesions at the onset, as well as the disease course, the severity, and the transmission rate when skin involvement is the unique manifestation of the COVID-19. More in general, our knowledge regarding the diagnostic accuracy of signs and symptoms to determine if a patient is affected by SARS-CoV-2 infection is still limited at the point that a recent Cochrane review concluded that, “based on currently available data, neither absence nor presence of signs or symptoms are accurate enough to rule in or rule out disease” [ 36 ].…”
Section: Resultsmentioning
confidence: 99%